Quantum simulation of 2D topological physics in a 1D array of optical cavities - Luo, Xi-Wang; Zhou, Xingxiang; Li, Chuan-Feng; Xu, Jin-Shi; Guo, Guang-Can; Zhou, Zheng-Wei (Nature communications, 2015)
Orbital angular momentum of light is a fundamental optical degree of freedom characterized by unlimited number of available angular momentum states. Although this unique property has proved invaluable in diverse recent studies ranging from optical communication to quantum information, it has not been considered useful or even relevant for simulating nontrivial physics problems such as topological phenomena. Contrary to this misconception, we demonstrate the incredible value of orbital angular momentum of light for quantum simulation by showing theoretically how it allows to study a variety of important 2D topological physics in a 1D array of optical cavities. This application for orbital angular momentum of light not only reduces required physical resources but also increases feasible scale of simulation, and thus makes it possible to investigate important topics such as edge-state transport and topological phase transition in a small simulator ready for immediate experimental exploration. A wide variety of interesting phenomena arise in 2D systems subject to external gauge fields, but these are sometimes challenging to verify experimentally. Here the authors propose a setup to simulate 2D physics with a 1D arrangement of cavities, by exploiting the orbital angular momentum of trapped photons.